Intestinal Infarction in COVID-19 Pandemic: A Case Series - Maryam Sarkardeh; Amin Dalili; Naser Tayyebi Meibodi; Mostafa Izanlu; Seyed Javad Davari-Sani; Saeed Moghaddamzade; Mehdi Jamalinik; Seyed Javad Hosseini; Javad Koushki; Ali Abedia (Iranian Society of Pathology, 2022)
Novel coronavirus disease 2019 (COVID-19) as a potential health risk factor continues to spread throughout the world. Although common symptoms include headache and respiratory symptoms, some studies have suggested that COVID-19 may cause coagulation disorders and thrombolytic events, disrupt blood flow to the visceral organs, and cause some complications such as mesenteric ischemia. The authors reported four cases of acute mesenteric ischemia associated with COVID-19 confirmed in patients hospitalized in Imam Reza Hospital (a COVID-19 referral center in Mashhad University of Medical Sciences, Mashhad, Iran). The authors described the pathological findings that may be associated with this infection. The authors collected clinical data, imaging, microscopic, and operative findings of four patients with severe COVID-19 infection and evidence of intestinal necrosis. These four cases that all had severe COVID-19 pneumonia simultaneously showed intestinal necrosis during the infection process, indicating a relationship between coronavirus and mesenteric vascular events. Physicians should be aware of thrombosis symptoms in the digestive system in patients with severe COVID-19 disease.